Fueling the rush – it’s all about caffeine - Lia Jiannine; Catherine Holen; Tobin Silver; Jose Antonio (Journal of the International Society of Sports Nutrition)
Background The primary aim of this study was to assess the effectiveness of an energy drink vs. a caffeine-matched control on measures of sustained attention.Methods Using a randomized, double-blind design (n = 107), subjects were assigned to an energy drink (C4 – Nutrabolt®) or a caffeine-matched control (200 mg caffeine). The following assessments were conducted before and approximately 45 minutes after consuming an energy drink or caffeine-matched control: psychomotor vigilance test (PVT), Memtrax (memory), handgrip strength, and wall-sit endurance.Results Both the energy drink and the caffeine-matched control improved pre vs. post for the PVT; however, there were no differences in the delta score. The energy drink group had a significant decrease in the Memtrax assessment (% correct) whereas reaction time increased with no change in the control; however, there were no differences in the delta score between groups for either the % correct score or reaction time. There were no significant differences in the handgrip or wall-sit assessments for either group.Conclusions Consuming 200 mg of caffeine, whether it is part of an energy drink or is a stand-alone ingredient, induces significant improvements in sustained attention and alertness (i.e. reaction time assessed by the PVT). However, there were no differences in memory, handgrip strength, or wall-sit endurance.